Measuring the Quality of Education and Health Services : The Use of Perception Data from Indonesia - Dasgupta, Basab; Narayan, Ambar; Skoufias, Emmanuel (2012)
Satisfaction surveys offer a potentially convenient and cost-effective means for measuring the quality of services. However, concerns about subjectivity and selection bias impede greater use of satisfaction data. This paper analyzes satisfaction data about health and educational services from the 2006 second round of the Governance and Decentralization Survey in Indonesia to assess whether satisfaction data can serve as reliable indicators of quality, despite dubiously high levels of reported satisfaction. The authors use an expectation disconfirmation model that posits that a user s satisfaction with a facility improves with the (positive) difference between the actual quality of the facility and the household s expected standard for quality, which is influenced by its socioeconomic characteristics. The findings show that, after taking into account the expectations of households, reported satisfaction does vary significantly with objective indicators of quality. The analysis also checks for possible selection bias affecting the results by using a two-stage selection model. The model yields policy-relevant insights into the aspects of service delivery that most affect satisfaction, highlights differences across rich and poor districts, and shows that once the role of expectations has been factored in, the variation in user satisfaction can be highly informative for policymakers and researchers alike.